A systematic review and meta-analysis on the global seroprevalence of Trichinella infection among wild boars. (September 2018) - Rostami, Ali; Riahi, Seyed Mohammad; Ghadimi, Reza; Hanifehpour, Hooman; Hamidi, Faezeh; Khazan, Hooshang; Ray Gamble, H.
Abstract: Trichinellosis, caused by the parasitic nematode Trichinella spp. is a widespread foodborne zoonotic disease and is a public health concern in many countries. Wild boar is the second most important source of trichinellosis for humans. We conducted a systematic review and meta-analysis to evaluate the global seroprevalence of Trichinella infection among wild boar. We searched five major databases for studies reporting Trichinella spp. seroprevalence in wild boar between January 1995 and January 2018. Inclusion and exclusion criteria were applied. A random-effects model was used to estimate the pooled seroprevalence of Trichinella in wild boar. A total of 21 studies involving 16, 327 wild boar from 15 countries were included in this meta-analysis. The pooled seroprevalence for Trichinella infection in wild boar was 6% (95% CI: 3–10%; 1084/16327). The estimated seroprevalence in North America was 9% (95% CI, 1–25%), in Europe 7% (95% CI, 3–13%), in Asia 3% (95% CI, 0.0–11%) and in Oceania 3% (95% CI, 2–4%). Geographical location, gender and age were not significantly associated with seropositivity. In sub-group analysis, the pooled seroprevalence of Trichinella infection in wild boar when ELISA was used as the diagnostic test (16%; 95% CI, 4–34%) was significantly higher when compared to western blot (4%; 95% CI, 0–12%). These results emphasize that wild boars are a potential source for acquisition of Trichinella infection in humans, and surveillance programs should be implemented in high-risk countries. Highlights: We evaluate the worldwide seroprevalence of Trichinella infection among wild boar. A total of 21 articles that included 16327 wild boar from 15 countries were assessed. The global seroprevalence in wild boar was 6% (95% CI: 3–10%).